Modulation of Cadmium Tolerance in Rice: Insight into Vanillic Acid-Induced Upregulation of Antioxidant Defense and Glyoxalase Systems - M.H.M. Borhannuddin Bhuyan (Plants, 2020)
Cadmium (Cd) is a toxic heavy metal that enters the human food chain from the soil via plants. Increased Cd uptake and translocation in plants alters metabolism andreduces crop production. Maintaining crop yield therefore requires both soil remediation andenhanced plant tolerance to Cd. In this study, we investigated the effects of vanillic acid (VA) on Cd accumulation and Cd stress tolerance in rice (Oryza sativa L. cv. BRRI dhan54). Thirteen-day-old rice seedlings treated with CdCl2 (1.0 and 2.0 mM) for 72 h showed reduced growth, biomass accumulation, and water and photosynthetic pigment contents, as well as increased signs of oxidative stress (elevated levels of malondialdehyde, hydrogen peroxide, methylglyoxal, and lipoxygenase) and downregulated antioxidant and glyoxalase systems. Cadmium-induced changes in leaf relative turgidity, photosynthetic pigment content, ascorbate pool size, and glutathione content were suppressed by VA under both mild and severe Cd toxicity stress. The supplementation of VA under Cd stress conditions also increased antioxidant and glyoxylase enzyme activity. Vanillic acid also increased phytochelatin content and the biological accumulation factor, biological accumulation co-efficient, and Cd translocation factor. Vanillic acid, therefore appears to enhance Cd stress tolerance by increasing metal chelation and sequestration, by upregulating antioxidant defense and glyoxalase systems, and by facilitating nutrient homeostasis.